LEXICOLOGY AND ITS BRANCHES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Linguistics—the scientific study of human language—is a dynamic and interdisciplinary field that influences diverse areas including education, anthropology, sociology, language teaching, cognitive psychology, philosophy, computer science, neuroscience, and artificial intelligence. Together with these latter disciplines, linguistics plays a foundational role in cognitive science, which explores the structure and function of human cognition. Despite its importance, many—even among the educated—have only a vague understanding of what linguistics entails. Some mistakenly equate linguists with multilingual individuals. In reality, linguistics examines the nature of language and communication. Humans have long been intrigued by language, yet we are still uncovering its complex mechanisms.